Agreement between muscle saturation breakpoints and lactate thresholds: Muscles comparison and sex difference in world-class Nordic skiers - Forot, J.; Schorderet, F.; Burdet, C.; Brocherie, F.; Millet, G. P. (Experimental Physiology, 2026)
Near-infrared spectroscopy (NIRS) has emerged as a potential alternative method for determination of breakpoints equivalent to lactate thresholds. However, the optimal NIRS location remains unclear, particularly in Nordic skiing, which requires both upper- and lower-limb contributions. This study aimed to evaluate the feasibility and accuracy of NIRS-derived breakpoints determination (i.e., BP1 and BP2) compared to first (LT1) and second (LT2) lactate thresholds and to compare different muscle sites in male and female world-class Nordic skiers. Fifty-two world-class Nordic skiers (29 males, 23 females) performed an incremental treadmill test on roller skis. NIRS sensors were located simultaneously on four muscles: vastus lateralis (VL), biceps femoris (BF), biceps brachii (BB), and triceps brachii (TB). Oxygen saturation (SmO2) was collected and analysed to detect BP1 and BP2 vs. LT1 and LT2. First, BP1 was too often undetectable or inaccurately detected, suggesting an unsuitable practical use. Second, BP2 was detected in VL (88.5%), BF (96.2%) and BB (86.5%) but not in TB (24.1%). Third, there was a very good accuracy (i.e., bias [95% CI] in heart rate between BP2 and LT2 in VL (-0.6 bpm [-8.9, 7.8]), BF (+1.3 bpm [-2.8, 4.2]) and BB (+1.0 bpm [-7.5, 9.5]). Finally, no significant differences were found between male and female athletes. NIRS appears as an effective non-invasive method for detecting breakpoint equivalent to LT2 in both male and female world-class Nordic skiers, especially if positioned on both BB and BF.